Male partners of infertile couples with congenital unilateral absence of the vas deferens are mainly non‐azoospermic. (7th January 2020) - Mieusset, Roger; Bieth, Eric; Daudin, Myriam; Isus, Francois; Delaunay, Boris; Bujan, Louis; Monteil, Laetitia; Fauquet, Isabelle; Huyghe, Eric; Hamdi, Safouane M.
Abstract: Background: Men with congenital unilateral absence of vas deferens were reported to be mainly azoospermic, with both unilateral renal absence and mutations in the cystic fibrosis transmembrane conductance regulator (CFTR) but some have neither. Objectives: To assess whether in infertile couples the male partners with congenital unilateral absence of vas deferens are mainly azoospermic men. Material and Methods: Retrospective study in a unique university hospital; reproductive, clinical, CFTR analysis and seminal data of male partners of infertile couples (from 1998 to 2018) were analysed. Diagnosis of congenital unilateral absence of vas deferens was based on transrectal ultrasounds (TRUS): complete or partial absence of one vas deferens with complete contralateral vas deferens confirmed in 63 men. Distribution of sperm count in three classes: azoospermia, oligozoospermia or normozoospermia. Ultrasound determination of renal status; seminal biomarkers assays; and search for CFTR mutations. Results: Among the 63 men, 39.7% displayed azoospermia, 27% oligozoospermia and 33.3% normozoospermia; 42% of the non‐azoospermic men (16/38) had previously obtained a natural pregnancy. We found unilateral renal absence in 17/59 patients (29%). Among 50 men with CFTR testing, five carried an allele associated with cystic fibrosis belonging to the 29 men without renal anomalies, indicating a high allelic frequency (8.6%). The 63 patients displayed high rates of surgical histories for undescended testicles or inguinal hernia, low values of semen volume and of total seminal glycerophosphocholine. Conclusions: Our results indicate that men with congenital unilateral absence of vas deferens mainly display oligozoospermia or normozoospermia and that they were previously fertile. They clearly confirm, first, that CFTR testing is recommended in congenital unilateral absence of vas deferens men and it should be mandatory for those with normal kidneys; and, second, that TRUS is needed for the diagnosis of congenital unilateral absence of vas deferens. As congenital unilateral absence of vas deferens may be present whatever the sperm count, biological warnings are represented by semen volume and seminal epididymal markers and clinical warnings by surgical histories of undescended testes or inguinal hernia.